Pengaruh Metode Demonstrasi terhadap Minat Belajar Pendidikan Agama Kristen dan Budi Pekerti Peserta Didik Kelas VII SMP Negeri 4 Siborongborong Tahun Pembelajaran 2023/2024 - Amelia Manullang; Hasudungan Simatupang; Pestaria Naibaho (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
The aim of this research is to determine the influence of students' interest in learning using the demonstration method. The research hypothesis is: "There is a difference in students' interest in learning in class VIII SMP N 4 Siborongborong for the 2023/2024 academic year before and after learning using the demonstration method. The population is all class VIII of SMP Negeri 4 Siborongborong, North Tapanuli Regency for the 2023/2024 academic year with 206 Protestant Christians consisting of 7 classes. The research sample was determined using the Purposive Sampling technique, namely 35 students in class VIII 3 as the experimental class using the demonstration method and class VIII 5 totaling 35 students as the control class using ordinary treatment (conventional class). This research method is the Quasy Experimental Design method using a Nonequivalent Control Group Design. The instrument used in this research was a 30-item questionnaire. Research data for the questionnaire was analyzed using the average difference test formula (N-Gain Score). It was found that the average value for the experimental class was 0.7454 in the high category. And the average value for the control class is 0.1481, which is in the low category. Then carrying out an independent test using the t test obtained a value of t = 15.168 > t table (α = 0.05; df = 68) = 2,000. Thus, it can be concluded that the research hypothesis is accepted, namely that there is a difference in students' interest in learning in class VIII of SMP N 4 Siborongborong for the 2023/2024 academic year before and after learning using the demonstration method.